ANALISIS PERBANDINGAN PREDIKSI KEBANGKRUTAN PERUSAHAAN DENGAN MENGGUNAKAN MULTIVARIATE DISCRIMINANT ANALYSIS DAN REGRESI LOGISTIK PADA PERUSAHAAN PERTAMBANGAN BATUBARA PERIODE 2010-2014 - Asnita, Rozza (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This research objective is to predict the bankruptcy in sector property and real estate which listed in Indonesia stock exchange: using discriminant analysis and logistic regression period 2010-2014. Sampling methods used in the research was purposive sampling. The hypothesis examination is tested by discriminant analysis and logistic regression analysis to determine significant differences in financial ratios such as current ratio, leverage ratio, net profit margin, debt to equity, operating profit margin, total asset turnover to distinguish a group of companies that are considered insolvent andnot statistically bankrupt on listed companies in Indonesia stock exchanges in coal mining sectorduring the period of 2010-2014. The data source of this research come from Indonesia Stock Exchange (IDX).The result of this research showed thatthe accuracy of the models using Discriminant analysiswas 80.4%and Logistic Regression Analysis was 88.2%. In the discriminantanalysis showed that the significant variables wereleverage ratioandnet profit margin. As for the second logistic regressionshowed that significantvariables wereleverage ratio, net profit margin, andtotal assets turnoverthat could affect the companys bankruptcy prediction coal mining sector in the period 2010 to 2014.